South Africa : 2012 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2012)
The Staff Report for the 2012 Article IV Consultation states that the policy pursued by South Africa has resulted in domestic and external stability, despite prevailing adverse circumstances. Given the volatile situation in the world economy as a whole-and Europe in particular-countercyclical monetary policy should be pursued, as fiscal revenue is likely to decline further. The report advocates utmost vigil from the South African Reserve Bank (SARB) to provide the much needed impetus to the economy by instilling investor confidence and a tight leash on future inflationary trends.